A review on concrete surface treatment Part I: Types and mechanisms. (1st February 2017) - Pan, Xiaoying; Shi, Zhenguo; Shi, Caijun; Ling, Tung-Chai; Li, Ning
Abstract: The application of surface treatments in concrete has been widely investigated over the past decades. Surface treatment technology has become more important in concrete structures especially in preventing deterioration and damage when exposed to extremely aggressive environments, and in further extending service life. This paper presents comprehensive details of four types of concrete treatments, including surface coating, hydrophobic impregnation, pore blocking surface treatment and multifunctional surface treatment. Additionally, the knowledge of their interaction mechanisms with cementitious substrate is presented and discussed. The advantages and drawbacks of each treatment as well as the influencing factors on the protective effects of surface treatments on concrete, such as air permeability, bonding strength and cracking resistance, are also discussed. Despite decades of study, the mechanisms of many newly developed surface treatments remain poorly understood. A deeper understanding of the chemical and physical reaction mechanisms is therefore essential, especially at micro-scale levels.